2023
DOI: 10.1088/1741-4326/ad0597
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive modelling of boron transport in the boundary plasma of WEST experiments with the impurity powder dropper

K. Afonin,
A. Gallo,
Y. Marandet
et al.

Abstract: Boron (B) powder injection is a potential alternative to glow discharge boronization as a wall conditioning method for tokamaks. This technique is currently being studied in WEST experiments, during which B powder is injected by an Impurity Powder Dropper (IPD) developed by PPPL. In order to interpret and analyze experimental data, and to help develop future experiments, a modelling workflow using a boundary plasma simulation (SOLEDGE-EIRENE) and powder ablation simulation (Dust Injection Simulator, DIS) was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Even though the powder injection site is localized to the edge, there was significant density peaking from ρ ⩽ 0.8. This increase in core density was not attributed directly to the ionization of the B powder as simulations from SOLEDGE-EIRENE and DIS of WEST discharges with B powder injection indicated that the B atoms become fully ionized at ρ > 0.9 [29]. Therefore, the peaking of the core density was likely due to modified particle transport rather than a modified particle source.…”
Section: Possible Mechanisms For Improved Confinementmentioning
confidence: 93%
“…Even though the powder injection site is localized to the edge, there was significant density peaking from ρ ⩽ 0.8. This increase in core density was not attributed directly to the ionization of the B powder as simulations from SOLEDGE-EIRENE and DIS of WEST discharges with B powder injection indicated that the B atoms become fully ionized at ρ > 0.9 [29]. Therefore, the peaking of the core density was likely due to modified particle transport rather than a modified particle source.…”
Section: Possible Mechanisms For Improved Confinementmentioning
confidence: 93%